Regulation of the pleiotropic effects of tissue resident mast cells - Huber, Michael; Freichel, Marc; Tsvilovskyy, Volodymyr; Bischoff, Stephan C. (The journal of allergy and clinical immunology, 2019)
Mast cells (MCs), which are best known for their detrimental role in patients with allergic diseases, act in a diverse array of physiologic and pathologic functions made possible by the plurality of MC types. Their various developmental avenues and distinct sensitivity to (micro-) environmental conditions convey extensive heterogeneity, resulting in diverse functions. We briefly summarize this heterogeneity, elaborate on molecular determinants that allow MCs to communicate with their environment to fulfill their tasks, discuss the protease repertoire stored in secretory lysosomes, and consider different aspects of MC signaling. Furthermore, we describe key MC governance mechanisms (ie, the high-affinity receptor for IgE [FcεRI]), the stem cell factor receptor KIT, the IL-4 system, and both Ca2+- and phosphatase-dependent mechanisms. Finally, we focus on distinct physiologic functions, such as chemotaxis, phagocytosis, host defense, and the regulation of MC functions at the mucosal barriers of the lung, gastrointestinal tract, and skin. A deeper knowledge of the pleiotropic functions of MC mediators, as well as the molecular processes of MC regulation and communication, should enable us to promote beneficial MC traits in physiology and suppress detrimental MC functions in patients with disease.